Reconfigurable low voltage low power dual-band self-cascode current-reuse quasi-differential LNA for 5G. (October 2019) - Hari Kishore, K.; Senthil Rajan, V.; Sanjay, R.; Venkataramani, B.
Abstract: This paper proposes a low noise amplifier (LNA) which can be reconfigured to operate in two frequency bands at low power. The LNA employs self-cascode devices in current-reuse configuration to enable lower supply voltage operation without compromising the gain. A quasi-differential structure is used to achieve high linearity and good common-mode rejection. The proposed LNA is designed to operate in (3.1–4.7 GHz: Band1) and (5.0–7.2 GHz: Band2) in the 5G frequency spectrum. It is implemented in 65 nm UMC-LL CMOS process technology using 0.6V, and its performance is evaluated using post layout, PVT and Monte Carlo simulations. The proposed LNA requires an area of 0.03276 mm 2 . The power dissipation, maximum gain, minimum noise figure, average IIP3, IIP2 of the LNA operating in Band1 and Band2 are found to be (0.97 ​mW, 17.6 ​dB, 2.20 ​dB, +0.72dBm, +46.49dBm) and (0.485 ​mW, 12.1 ​dB, 3.31 ​dB, +0.12dBm, +42.60dBm) respectively.